Development of E-Book «Children’s Literature» Using Google Presentations - Kharkivska, Alla A. (International Journal of Psychosocial Rehabilitation, 2020)
In the process of scientific research, the authors have determined that Google presentations are more convenient for the development of e-book «Children's literature». In the article, the researchers present in detail all stages and peculiarities of the development of e-book «Children's Literature» with the help of Google presentations from the beginning of the creation of own accounts to the publication of the textbook. The authors prove that the use of electronic textbooks represent a significant advantage for the future philology professionals in Ukrainian language and literature is since it allows to carry out text referencing using the stylus to allocate the fragments necessary to combine a short and all-embracing story from a large volume of short stories and novels. The authors conclude that „Children's Literature‟ e-book, developed and implemented in the educational process of future specialists in philology disciplines, », and being further advancing with the help of Google presentations, will allow improving the quality of studies and raising interest of students in studying literature, as well as promoting the diversification of educational activities through the use of a significant amount of multimedia textbook and illustrative material. The scholars contend the prospects of further researchin the development of not only«Children's literature» e-book, but also the electronic writing books and vocabularies.